In the Face of Climate Change: Perceptions of Interconnections Between Community Resilience and Community Sustainability - Felix N. Fernando; Meg Maloney; Lauren Tappel (Urban Science)
Community resilience and community sustainability have increasingly become popular topics of research separately and together. The aim of this article is to elucidate the perceived interconnections between community sustainability and community resilience using Dayton, OH, as a case study. This article largely examines the perceived interconnections between climate change mitigation and climate adaptation initiatives within sustainability and the three-class typology of resilience (basic, adaptive, and transformative). A two-pronged data collection effort designed using the Community Capitals Framework was carried out to recruit a broad group of participants. A multi-chain referral sampling process (and subsequent snowball sampling) was initiated subsequently. The data were gathered through semi-structured interviews with 75 participants. The interviews were analyzed using a three-tiered deductive structural coding approach. The findings elucidate the multifaceted and multi-dynamic nature of interconnections between community sustainability and resilience. Compared to literature that contends one concept to be a sub-concept of the other (resilience as a sub-concept of sustainability and vice versa), the findings of this study demonstrate that the interconnections between community sustainability and resilience are layered and complex. Some level of resilience was perceived as necessary for community sustainability. The implications of the findings on creating integrated sustainability and resilience strategies are discussed.